PENTINGNYA LAKU SEMEDI BAGI PEMANGKU DAN PINANDHITA - Poniman, Romo (JURNAL YOGA DAN KESEHATAN, 2020)
The highest desirable behavior for the followers of Kejawen is, among others, exercise, exercise which in this case requires a routine training. Having a high mysticism can be more sensitive to feelings in overcoming and accepting conditions. But to have a high level of mysticism requires a special discipline of life and behavior to achieve this situation. In practicing self-discipline, a follower of Kejawen should often do Semedi. By meditation in this case it is a special behavior to train oneself to join oneself with Gusti. Before doing Semedi, you should realize the concept of the existence of the Three Realms in the human body. After knowing it, the Semedi training can be carried out to find the peak of success that will eventually be trained to have a sensitive and holy mind so that peace is felt.